Thermal Optimization of Earth Bricks Using Néré Husk (Parkia biglobosa) - Magnouréwa Josiane Tossim; Elhadji Dieng; Kpatchaa Lidawou Bafei; Cyprien Coffi Aholou; Yawovi Mawuénya Xolali Dany Ayité (Construction Materials)
Integrating local, bio-sourced materials, such as earth and agricultural waste like dwarf hulls, is a sustainable solution to the challenges of climate change and increasing urbanization. The use of bio-based materials such as néré husk (Parkia biglobosa) in the manufacture of compressed earth bricks is a sustainable alternative for improving their thermal performance. This study assesses the impact of adding hulls in different forms (fine powder < 0.08 mm, aggregates from 2 mm to 5 mm, and aqueous maceration) on the thermal conductivity and effusivity of bricks. The tests were carried out using the asymmetric hot plane method, applying a constant heat flux and measuring the temperature variation via a thermocouple. Three samples of each formulation were analyzed to ensure the reliability of the results. The results show that the addition of fine powdered husk reduces the thermal conductivity of the bricks to 0.404 W/m.K and their effusivity to 922.2 W/(Km2) s1/2, compared with 0.557 W/m.K and 1000.32 W/(Km2) s1/2 for the control bricks. The addition of coarser aggregates (2 mm–5 mm) gives intermediate values (0.467 W/m.K and 907.99 W/(Km2) s1/2). Aqueous maceration, on the other hand, results in an increase in thermal conductivity to 0.614 W/m.K. These results confirm that the shape and method of incorporation of the husk influence the thermal performance of the bricks, with fine powder offering the best thermal insulation. This approach highlights the potential of bio-based materials for eco-responsible construction.